الإمام أبو داود سليمان بن نجاح اختياراته في مسائل الضبط القرآني من خلال كتابه أصول الضبط وما جرى به عمل المصاحف من أول الكتاب إلى أحكام ضبط النون الساكنة - بوغزالة, عبد الكريم (University of Eloued جامعة الوادي, 2014)
كانت الكتابة الأولى للمصاحف في عهد الصحابة رضوان الله عليهم دون نقط ولا شكل، وفي آخر زمن الصحابة رضي الله عنهم زيد في المصحف النقط، فوضعت الحركات، من طرف أبي الأسود الدؤلي في نقطه المدور، ثم من طرف الخليل بن أحمد الفراهيدي في نقطه المطول، وهذا فيما يخص نقط الإعراب، وكذا نقط الإعجام الذي هو نقط الحروف، الذي ينسب ليحيى بن يعمر ونصر بن عاصم. وهكذا تتابع العلماء في وضع علامات لضبط الكلمات القرآنية، من أجل التيسير على الناظر في المصحف الشريف، وكان بينهم اختلاف في كثير من علامات الضبط. والبحث يتحدث عن إمام من أئمة الأندلس الكبار، يعرف بشخصيته، وحياته العلمية، ويبين مكانته وثناء العلماء عليه وعلى كتبه، ويعرف بكتابه الذي ألفه في علم الضبط القرآني، وهو من أصول هذا الفن. هذا الإمام هو أبو داود سليمان بن نجاح، ألف كتابه: أصول الضبط، بين فيه كيفية شكل الكلمات القرآنية، وأورد فيه خلاف العلماء ومذاهبهم في ذلك. ويعرض البحث كذلك لاختيارات هذا الإمام في ضبط الحروف والكلمات القرآنية، مبينا أسس اختياره، وما عليه عمل المصاحف اليوم. The first writing of copies of the Koran was without dots in the era of the Companions, God bless them, and in the last time of them dots added and diacritical marks have been placed by Abou Alasouad Edoali at his circular dots, then by Khalil bin Ahmed Faraaheedi at his prolonged dots, this is about dots of inflection, as well as dots of letters which attributed to Yahya bin Yaamr and Nasr bin Asim. So scholars placed marks to adjust the Koranic words, in order to make them easier for the viewer in the Holy Koran, and among them was a difference in many marks of vowelization. The research talks about a great imam of the imams of Andalusia who is known his personality, and his scientific career, and it shows the stature and scholars praise on him and his books. He is known by his book that he composed in Koran science and it is one of origins of this art. This Imam is Abu Dawood Sulaiman bin Najah. He composed his book: Origins of vowelization and its method on the shortness. He showed the way of diacritic of the Koranic words, and he cited the dispute of scholars and their doctrines in it, with justification. The research also displays the choices of this imam in vowelizing the letters and the koranic words showing the foundations of his choice and copies of the Koran work today.
مقال بمجلة البحوث والدراسات
Keywords: الإمام أبو داود سليمان بن نجاح - الضبط القرآني - مصاحف